Sensorimotor vs. Motor Upper Limb Therapy for Patients With Motor and Somatosensory Deficits: A Randomized Controlled Trial in the Early Rehabilitation Phase After Stroke - De Bruyn, Nele; Saenen, Leen; Thijs, Liselot; Van Gils, Annick; Ceulemans, Eva; Essers, Bea; Lafosse, Christophe; Michielsen, Marc; Beyens, Hilde; Schillebeeckx, Fabienne; Alaerts, Kaat; Verheyden, Geert (Frontiers in Neurology, 2020)
Background: Somatosensory function plays an important role in motor learning. More than half of the stroke patients have somatosensory impairments in the upper limb, which could hamper recovery. Question: Is sensorimotor upper limb (UL) therapy of more benefit for motor and somatosensory outcome than motor therapy? Design: Randomized assessor- blinded multicenter controlled trial with block randomization stratified for neglect, severity of motor impairment, and type of stroke. Participants: 40 first-ever stroke patients with UL sensorimotor impairments admitted to the rehabilitation center Intervention: Both groups received 16 hours of additional therapy over four weeks consisting of sensorimotor (N=22) or motor (N=18) UL therapy. Outcome measures: Action Research Arm test (ARAT) as primary outcome, and other motor and somatosensory measures were assessed at baseline, post-intervention and after four weeks follow-up. Results: No significant between-group differences were found for change scores in ARAT or any somatosensory measure between the three time points. For UL impairment (Fugl-Meyer assessment), a significant greater improvement was found for the motor group compared to the sensorimotor group from baseline to post-intervention (mean (SD) improvement 14.65 (2.19) versus 5.99 (2.06); p=0.01) and from baseline to follow-up (17.38 (2.37) versus 6.75 (2.29); p=0.003). Conclusion: UL motor therapy may improve motor impairment more than UL sensorimotor therapy in patients with sensorimotor impairments in the early rehabilitation phase post stroke. For these patients, integrated sensorimotor therapy may not improve somatosensory function and may be less effective for motor recovery. Trial registration: The trial is registered at clinicaltrials.gov NCT03236376.